Efficay of the use of Dihydroergotamine in the Management of Migraine Attacks: A Systematic Review with Meta-Analysis - Pacheco Barrios, Kevin (2018)
Objective: To evaluate the clinical efficacy of the use of ergotamines in the management of migraine attacks. Methods: A systematic search was performed in the MEDLINE and CENTRAL databases until May 2018, duplicates were eliminated, and studies were selected independently, the quality of the studies that met the inclusion criteria was evaluated. Subsequently, the results were extracted to perform a meta‐analysis of the comparable studies. The random effects model was used, and heterogeneity was assessed with I2. Results: Three studies were found that compared DHE (1mg SC) versus sumatriptan (6mg SC) and one against chlorpromazine (12.5mg IV). In one of the studies, the reduction at 2 hours in the mean intensity of headache was significantly better among those treated with chlorpromazine (p < 0.005). Besides, a meta‐analysis (2 RCTs, n = 347) with a random‐effects model was performed, the pain‐free outcome at 2 hours was evaluated in patients with migraine attacks. Higher freedom of pain was found at 2 hours in the group of patients with triptans treatment (138/175 = 78.8%) compared to DHE (103/172 = 59.8%) (RR = 3.64, 95% CI = 1.03 ‐ 12.90). Conclusion: With few studies of low‐medium quality, it was found that treatment with triptans and antiemetics are superior to DHE in patients with migraine attacks. It is recommended to carry out more high‐quality clinical trials to prove the use of DHE for the treatment of migraine attacks.